Entrepreneurial behavior is reviewed from financial literacy and use of social media with self efficacy as a moderating variable - Aprilia, Novita; Surjanti, Jun; Susanti, (Technium Social Sciences Journal, 2024)
The aim of this research is to see how financial literacy and use of social media impact entrepreneurial behavior, with self-efficiency as a moderating variable. In this study, the population consisted of students from the economics and business faculties at Surabaya State University. The purposive sample selection method was used to select the sample, which resulted in 44 students as the sample. The research tool used in this study was a questionnaire distributed to students involved in faculty-funded ventures. This business lasts for one year and can be done online or offline. This research uses the structural equation model (SEM) hypothesis, which is supported by the partial least squares (PLS) analysis method. The results of this research show that financial literacy influences entrepreneurial behavior, social media use influences entrepreneurial behavior, and the self-efficiency moderating variable cannot strengthen the influence of financial literacy on entrepreneurial behavior, while the self-efficiency moderating variable can strengthen the influence of social media use on entrepreneurial behavior. Keywords: Financial Literacy, Use of social media, entrepreneurial behavior, self-efficacy